What and How Hybrid Forms of Christian Social Enterprises Are Created and Sustained in Cambodia? A Critical Realist Institutional Logics Perspective - Kimura, Rikio (Religions, 2021)
On top of the well-known dilemma of social enterprises as hybrid organizations, the form in which they struggle to balance business viability and the fulfillment of social missions, faith-based social enterprises have an added dimension: their spirituality manifested as organizational culture and practices based on their spiritual values and mission to spread their faith. By employing critical realist institutional logics and an identity-based and biographical approach to social entrepreneurship, this study identifies a typology of different hybrid forms of Christian social enterprises in Cambodia and the tensions associated with them. Moreover, this study explores how and why their social entrepreneurs have created and sustained such forms. I analyzed the qualitative data of 12 Christian social enterprises mainly from interviews with their entrepreneurs. Broadly speaking, the analysis revealed that the hybrid forms of these enterprises depend on the entrepreneurs’ agency, which is influenced by their biographies and contexts. Particularly, in addition to the entrepreneurs’ possession and enactment of multiple identities, boards of directors (as part of the context) and their accountability pressures are crucial for Christian social enterprises to achieve the triple bottom line of business viability, social missions, and spiritual outcomes.